The Integration of Phonetic Knowledge in Speech Technology - Barry, William J.; Dommelen, Wim A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
Continued progress in Speech Technology in the face of ever-increasing demands on the performance levels of applications is a challenge to the whole speech and language science community. Robust recognition and understanding of spontaneous speech in varied environments, good comprehensibility and naturalness of expressive speech synthesis are goals that cannot be achieved without a change of paradigm. This book argues for interdisciplinary communication and cooperation in problem-solving in general, and discusses the interaction between speech and language engineering and phonetics in particular. With a number of reports on innovative speech technology research as well as more theoretical discussions, it addresses the practical, scientific and sometimes the philosophical problems that stand in the way of cross-disciplinary collaboration and illuminates some of the many possible ways forward. Audience: Researchers and professionals in speech technology and computational linguists.
Phonetic Knowledge in Speech Technology -- Can Phonetic Knowledge be Used to Improve the Performance of Speech Recognisers and Synthesisers? -- Prosodic Models, Automatic Speech Understanding, and Speech Synthesis: Towards the Common Ground? -- Phonetic Time Maps -- Introducing Phonetically Motivated, Heterogeneous Information into Automatic Speech Recognition -- Introducing Contextual Transcription Rules in Large Vocabulary Speech Recognition -- From Here to Utility -- Pronunciation Modeling -- Phonetic Knowledge in Text-to-Speech Synthesis -- Is Phonetic Knowledge of Any Use for Speech Technology?.
Keywords: LINGUISTICS; TRANSLATORS (COMPUTER PROGRAMS).; APPLIED LINGUISTICS; COMPUTATIONAL LINGUISTICS; LINGUISTICS; COMPUTATIONAL LINGUISTICS; LANGUAGE TRANSLATION AND LINGUISTICS; APPLIED LINGUISTICS